Analysis and test of splitting failure in the cutting process of cabbage root - Dongdong, Du; Jun, Wang; Shanshan, Qiu (International Journal of Agricultural and Biological Engineering, 2015)
Cabbage harvester is very useful to replace the manual cabbage harvesting in China. The cutter with single-point clamping way can reduce the maximum and the average cutting force effectively, but may increase the splitting failure. In this study, the mechanics model of cabbage root with single-point clamping way in cutting process was established. According to the analysis of mechanics model, when the sheer stress exceeded the sheer strength (τa>τ0), splitting failure began to occur. Meanwhile, if the maximum normal stress exceeded the tensile strength (σmax>σ0), the splitting failure would further become riving failure. The positions of splitting failure would almost locate at the cutting depth l equaled to R+r (l=R+r). To reduce the splitting failure, single factor and multi-factor cutting tests about the effect of sliding angle, cutting speed and cutting diameter on splitting failure were carried out. The results showed that the splitting failure would reduce with the increase of sliding angle, cutting speed and cutting diameter. Sliding angle, cutting speed, cutting diameter and the interactions of cutting speed with sliding angle and cutting diameter had significant effect on splitting failure level, and the interaction of sliding angle with cutting diameter and the 3 factors’ interaction had no effect. To minimize splitting failure levels, the best cutting combination was that: sliding angle 40°, cutting speed 300 mm/min and cutting diameter 35 mm. This research can provide a basis of how to design a cutter for the cabbage harvester including the optimized cutting combination. Keywords: cabbage, cutting process, splitting failure, mechanics analysis, tests DOI: 10.3965/j.ijabe.20150804.1723 Citation: Du D D, Wang J, Qiu S S. Analysis and test of splitting failure in the cutting process of cabbage root. Int J Agric & Biol Eng, 2015; 8(4): 27－34.